Developing Sustainable Corporate Social Responsibility Based on Islamic Perspective - Noor Shodiq Askandar; Junaidi Junaidi; Masyhuri Machfudz (University of Islam Malang, 2018)
Corporate social responsibility (CSR) issues are constantly evolving nowadays since social and ethical issues have received public attention and high regulatory pressure regarding this issue. Malang Regency has implemented the CSR since long time ago. Every company in Malang Regency has obligated to implement CSR program. The potential of CSR in Malang Regency itself is very big when viewed from the total number of companies that reaches 1,350 companies both in small and large scale. There are also 76 sugar factories in Indonesia and most of them are located in East Java, including Kebon agung which located in Malang Regency. This study can be classified as narrative qualitative research with Kebon Agung as a research objective. This study used formal interviews, and participant observation as data collected method. This study concluded that Economic motives considered as the most appealing CSR program from both the company and the CSR target group perspective. Economic development is impossible without a good education. Education is indispensable to economic development. The financial business incentives of CSR program should follow by providing good education, training, and mentoring in purpose to achieve its effectiveness. To get the better knowledge, the education, training, and mentoring program should collaborate with the regulator, academicians, and professional.